The Process of Making Animated Videos on Chemical Theory and Colloid Systems Using the CapCut Application - Khairiawati, Lailan (International Journal of Science Education and Science, 2025)
In the current era of information technology, the learning process has begun to implement interesting innovations. The learning process is not only through direct or face-to-face communication with the lecture method that creates a feeling bored and fed upon students. The Covid-19 pandemic that occurred in 2020 changed the entire order of human life, starting from the economic, social, religious to the education system. During the Covid-19 pandemic, some of the teachers at school were not ready to carry out the learning process through interactive media such as learning videos to support the learning process from home. The purpose of this research is to find out how to make learning animated videos using CapCut. The method used is the method of literature regarding the making of an animated video for learning chemistry on colloidal system material using the CapCut application. The results of this study are in the form of animated videos learning chemistry colloid system material using the capcut application to facilitate students and educators in the teaching and learning process